Thymol and carvacrol against Klebsiella: anti-bacterial, anti-biofilm, and synergistic activities—a systematic review - Farhadi, Kousha; Rajabi, Erta; Varpaei, Hesam Aldin; Iranzadasl, Maryam; Khodaparast, Sepideh; Salehi, Mohammadreza (Frontiers in Pharmacology, 2024)
Introduction: Klebsiella poses a significant global threat due to its high antibiotic resistance rate. In recent years, researchers have been seeking alternative antimicrobial agents, leading to the introduction of natural compounds such as monoterpenes, specifically thymol and carvacrol. This review aims to illustrate the potential antimicrobial, anti-biofilm, and synergistic traits of thymol and carvacrol in combat against Klebsiella. Methods: Searching PubMed, Scopus, and Web of Science, we reviewed available evidence on the antibacterial effects of thymol, carvacrol, or combined with other compounds against Klebsiella until May 2024. Reference checking was performed after the inclusion of studies. Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), fractional inhibitory concentration (FIC), and anti-biofilm activity were gathered, and MBC/MIC ratio was calculated to assess the bactericidal efficacy. Results: We retrieved 38 articles out of 2,652 studies screened. The gathered data assessed anti-microbial activity of thymol, carvacrol, and both compounds in a total of 17, 10, and 11 studies, respectively. The mean (± standard deviation) non-weighted MIC was 475.46 µg/ml (±509.95) out of 60 MIC for thymol and 279.26 µg/ml (±434.38) out of 68 MIC for carvacrol. Thymol and carvacrol showed anti-biofilm activities in the forms of disruption, inhibition, and mass reduction of biofilms. The MBC/MIC ratio was lower than 4 in 45 out of 47 cases, showing high bactericidal efficacy. FIC values were gathered for 68 combinations of thymol and carvacrol with other compounds, and they were mostly synergistic or additive. Conclusion: Thymol and carvacrol alone or in combination with other compounds, specifically known antibiotics, show great antimicrobial activity.